Doctors of the dark side - Davis, Martha (Producer); Harris, Mark Jonathan, 1941-; Ruehl, Mercedes; DODS Productions Inc.; Soundview Media Partners ([United States] : DODS Productions Inc., 2011)
This film is the first feature-length documentary about how health care professionals actively implemented and covered up the tortures in Abu Ghraib, Guantanamo and the CIA Black Sites. The film shows how the torture of detainees could not continue without the assistance of these American doctors. The little-known story is told by military, legal and medical experts and portrayed through staged demonstrations as spelled out in declassified government documents.
"A deeply troubling documentary ... highly recommended."--
Originally released as a motion picture in 2011
Narrator, Mercedes Ruehl.
Cinematographer, Lisa Rinzler ; editor, M. Trevino ; music, Maxim Moston.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed September 27, 2019)
Keywords: Abu Ghraib Prison; Prisoners of war -- Medical care -- Moral and ethical aspects; Medicine, Military -- Moral and ethical aspects; Medical personnel -- Professional ethics -- United States; Torture -- Moral and ethical aspects; Prisoners of war -- Abuse of -- Iraq; Prisoners of war -- Abuse of -- Afghanistan; Prisoners of war -- Abuse of -- Cuba; War on Terrorism, 2001-2009 -- Moral and ethical aspects; Guantánamo Bay Naval Base (Cuba); War crimes -- United States -- History -- 21st century; Social problem films; Feature films; Documentary films; Nonfiction films; Internet videos; Streaming video